2015
DOI: 10.1370/afm.1814
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Patients Hastening Death by Voluntarily Stopping Eating and Drinking

Abstract: PURPOSELittle is known about the role family physicians play when a patient deliberately hastens death by voluntarily stopping eating and drinking (VSED). The purpose of this study was to gain more insight for family physicians when confronted with patients who wish to hasten death by VSED. We aimed to describe physicians' involvement in VSED, to describe characteristics and motives of their patients, and to describe the process of VSED in terms of duration, as well as common symptoms in the last 3 days of lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(108 citation statements)
references
References 25 publications
5
91
0
12
Order By: Relevance
“…This prevalence is similar as that reported by nurses working in hospices in Oregon,2 and less than that by Dutch family physicians 8. In this survey, we revealed that Japanese patients were also trying to implement VSED to hasten their deaths themselves.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This prevalence is similar as that reported by nurses working in hospices in Oregon,2 and less than that by Dutch family physicians 8. In this survey, we revealed that Japanese patients were also trying to implement VSED to hasten their deaths themselves.…”
Section: Discussionsupporting
confidence: 84%
“…Physicians confronted with VSED may experience moral conflict in respecting the patient’s self-determination and allowing patient suicide, and could be reluctant to support the patient in a path leading to death 8. Supportive interventions, such as continuous deep sedation (CDS), have been debated in regards to reducing patients’ refractory symptoms and suffering associated with hunger and fatigue during the VSED process 8–10…”
Section: Introductionmentioning
confidence: 99%
“…Even in environments where PAD is legally available, some patients will still preferentially choose VSED. 6 The psychological impact of voluntarily choosing VSED among a range of other last resort possibilities is very different from having this choice imposed upon a patient who would have preferred PAD. Although A.A. appreciated having an escape from suffering under his control, he found VSED to be more cruel and absurd than meaningful.…”
mentioning
confidence: 99%
“…There are also important differences: (1) VSED takes longer and is harder to accomplish, as patients get very thirsty as it unfolds; (2) the doctor's role in VSED is more indirect (38% of patients in the study by Bolt et al had no physician involvement), 6 where physician involvement is more direct in PAD (doctor provides the means but the patient must independently take the medication); (3) the esthetics of the processes are different; VSED usually takes 1 to 2 weeks with a series of medical and social challenges, whereas PAD is a definitive medical intervention with death expected in minutes to hours; and (4) if PAS is chosen in states where it is illegal, both the clinician and the family must keep a major secret to prevent legal complications, potentially complicating grief, whereas VSED can be openly and legally practiced anywhere in the United States.…”
mentioning
confidence: 99%
“…VSED is physiologically similar to discontinuation of artificial nutrition but presents unique symptom management, anticipatory guidance for families, and ethical underpinnings (because it is not withdrawal of invasive medical intervention). VSED further differs from other palliative measures of last resort such as physician‐assisted dying or proportionate palliative sedation because it can be accomplished without physician input and may be implemented in an individual with a serious but not imminently terminal illness (e.g., early dementia) . This is not to say that clinicians should be inactive in the process because they should be part of the initial assessment, provide anticipatory guidance, and work to alleviate additional suffering once VSED is initiated.…”
Section: Defining Voluntary Stopping Of Eating and Drinkingmentioning
confidence: 99%